2011
DOI: 10.5488/cmp.14.33601
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of hard spheres: structure and effective density according to the potential distribution theorem

Abstract: We propose a new type of effective densities via the potential distribution theorem. These densities are for the sake of enabling the mapping of the free energy of a uniform fluid onto that of a nonuniform fluid. The potential distribution theorem gives the work required to insert a test particle into the bath molecules under the action of the external (wall) potential. This insertion work W ins can be obtained from Monte Carlo (MC) simulation (e.g. from Widom's test particle technique) or from an analytical t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that the ZSEP theory gives accurate structures and properties of hard spheres 23 that are dependable and with accuracies ascertained by simulation data from low to high densities (up to ρ * = 0.90). 17 In summary, for the triplet ln y (3) bca (ω) of contacting hard spheres, we use the MC data from Mueller and Gubbins (Option (a) above). For the pair ln y (2) ca (d)) at contact, we use the Carnahan-Starling equation, Eq.…”
Section: F Considering the Kirkwood Charging Formalismmentioning
confidence: 99%
“…It has been shown that the ZSEP theory gives accurate structures and properties of hard spheres 23 that are dependable and with accuracies ascertained by simulation data from low to high densities (up to ρ * = 0.90). 17 In summary, for the triplet ln y (3) bca (ω) of contacting hard spheres, we use the MC data from Mueller and Gubbins (Option (a) above). For the pair ln y (2) ca (d)) at contact, we use the Carnahan-Starling equation, Eq.…”
Section: F Considering the Kirkwood Charging Formalismmentioning
confidence: 99%